On payday lending: Identifying effective regulation measures - Campbell, Steele; Kalenkoski, Charlene; Lauderdale, Mitzi (Journal of Social Economics Research, 2023)
Many governments adopt regulations designed to prevent consumers from participating in specific financial markets or to limit the negative externalities of such markets. However, relatively little effort has been put into determining the efficacy of such regulatory measures. In many cases, effectively comparing these regulatory measures is limited by variations in preferences and cultures across nationalities. However, the United States may represent a unique situation where preferences and cultures are more homogenous across state lines than across international boundaries. As such, a comparison of the efficacy of these laws may yield a better understanding of which measures prove more effective than others. One such financial market that has received such attention is the payday lending industry, which is part of the broader subprime credit market. In the United States, each individual state has its own laws regarding subprime lending. The analysis in this paper finds that while some legal regimes have a relationship to positive or negative outcomes among consumers, others seem to have no relationship at all.